Necessidades formativas dos professores do ciclo I do Ensino Fundamental de Presidente Prudente - SP - Yamashiro, Carla Regina Calone [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Este trabalho está vinculado à linha de pesquisa Políticas Públicas, Organização Escolar e Formação de Professores e tem como preocupação, investigar sobre as ações de formação contínua de professores e as necessidades formativas docentes, elementos importantes para a construção de uma identidade profissional crítica e reflexiva. O problema em pauta nesta pesquisa é como contemplar as necessidades formativas docentes nos projetos de formação contínua de professores, tendo em vista a importância da função docente na construção de uma sociedade mais justa e democrática. Esta pesquisa pretende, então, responder o seguinte questionamento: quais são as necessidades formativas dos professores estaduais, do ciclo I do Ensino Fundamental, do município de Presidente Prudente, quando levamos em consideração os outros aspectos envolvidos no desenvolvimento profissional docente, além da formação técnica-pedagógica, isto é: as suas condições sócio-econômicas, a sua formação profissional, as suas condições de trabalho e as suas expectativas sobre a função docente e a formação contínua...

This work is related to the research area “Public Policies, School Organization and Teachers’ Training”. Its aim is to perform research about teachers’ continuous training projects and teachers’ training needs. Those are very important elements in the construction of a critical and thoughtful teaching. The aim of this work is to study how to incorporate the teachers´ training needs in the projects of teachers´ continuous education taking into account the important role that teaching has in the construction of a fairer and democratic society. This research intends to answer the following question. Taking into account aspects, other than the technical-pedagogic, that take part in the teachers´ professional development, i.e., taking into account the teachers’ social-economic situation, their professional training and work conditions as well as their expectations about teaching and continuous training, what are the training needs of the teachers of the so-called “Ciclo I” (First Stage) of teaching in state schools in the city of Presidente Prudente, São Paulo state, Brazil. Therefore, this work has as its general aim. Therefore, this research has as its general aim to provide some contribution to the area of teachers’ continuous training through the analysis of the teachers’ training needs. As its more... (Complete abstract click electronic access below)
Keywords: Educação; Politicas publicas; Professores - Formação; Teachers’ continuous training